Eye Movement Strategies Involved in Face Perception. (November 2013) - Walker-Smith, Gail J; Gale, Alastair G; Findlay, John M
Recordings were made of the eye fixations of three subjects in two tasks involving black-and-white photographs of faces. In the first task, subjects matched a test face with a previously viewed target face; in the second task, subjects compared two simultaneously presented faces. The eye movements were recorded with a corneal reflection technique. Each subject showed an individual fixation strategy for the tasks; in particular each subject had one or more preferred facial features which were viewed foveally in both tasks. The subjects also showed some tendency to use a regular sequential pattern of eye movements. However, the sequences used differed from one task to the other. Although some aspects of the results support the scanpath hypothesis of Noton, it is suggested that an alternative interpretation is possible.